β-Sheet Breaker Peptide-HPYD for the Treatment of Alzheimer's Disease: Primary Studies on Behavioral Test and Transcriptional Profiling - Liu, Weiying; Sun, Fengxian; Wan, Moxin; Jiang, Fang; Bo, Xiangyu; Lin, Laixiang; Tang, Hua; Xu, Shumei (Frontiers in Pharmacology, 2018)
Background: Alzheimer's disease (AD), is a progressive neurodegenerative disease that is characterized by cognitive loss. Most researchers believe that aggregation and accumulation of β-amyloid peptides (Aβ) in brain cells are the central pathological hallmark of this disease. Methods: Based on the amyloid hypothesis, a 10 amino acids β-sheet breaker peptide HPYD (His-Lys-Gln-Leu-Pro-Phe-Tyr-Glu-Glu-Asp) was designed according to the structure and sequence of the previous designed peptide H102. Accelerated stability test, thioflavine T (ThT) fluorescence spectral analysis and transmission electron microscopy (TEM) imaging were performed to detect the stability and inhibitory effects on the aggregation of Aβ1−42 by H102 and HPYD. FITC-labeled HPYD was first tested to determine whether it could be transferred along the olfactory pathway to the brain after nasal administration to mice. Subsequently, the Morris Water Maze (MWM) test for behavioral analysis was used to investigate the learning and memory ability of APP/PS1 transgenic mice by HPYD. Immunohistochemistry and western blot analysis was performed to determine the role of HPYD on Aβ and APP protein levels. In addition, microarray analysis was used to evaluate the effect of HPYD on gene expression in AD mouse models. Results: Our in vitro results demonstrated that HPYD had enhanced stability and inhibitory effects on Aβ1−42 aggregation compared to H102. HPYD could be delivered into the brain through nasal administration and improved the learning and memory ability in APP/PS1 transgenic mouse models by reducing Aβ and APP protein levels. In addition, microarray analyses suggested that several genes related to the inflammatory pathway, AD and gluco-lipid metabolism were dysregulated and could be restored to almost normal levels after HPYD administration to mice. Conclusions: Our results demonstrated that HPYD could be a potential therapeutic drug candidate for the treatment of AD.